2019
DOI: 10.1108/yc-01-2019-0943
|View full text |Cite
|
Sign up to set email alerts
|

Engaging customers through credible and useful reviews: the role of online trust

Abstract: Purpose Electronic commerce (e-commerce) is growing rapidly and the e-retailers are finding it pertinent to enhance customers’ online shopping experiences and engage them with e-commerce portals. Against this backdrop, the purpose of this study is to develop a conceptual model of customer engagement, where credibility and usefulness of online reviews are found to trigger the adoption of reviews and customer trust that augments customer engagement. Design/methodology/approach A survey method design has been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
2
23
2
Order By: Relevance
“…Previous studies acknowledge such a relationship-for example, a study by Lee and Hong (2019) showed that review helpfulness influences eWOM adoption. Other studies found similar results, including Shaheen et al (2019) and Ruangkanjanases et al (2021).…”
Section: The Mediating Effect Of Ewom Adoptionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previous studies acknowledge such a relationship-for example, a study by Lee and Hong (2019) showed that review helpfulness influences eWOM adoption. Other studies found similar results, including Shaheen et al (2019) and Ruangkanjanases et al (2021).…”
Section: The Mediating Effect Of Ewom Adoptionsupporting
confidence: 76%
“…Lis and Horst (2013) researched the relationship between trustworthiness and referral credibility and discovered that recipients of eWOM reviews depend heavily on the sender's trustworthiness. Trust is believed to be based on someone's willingness or capacity to rely on another person (Bulut & Karabulut, 2018;Shaheen et al, 2019).…”
Section: Trustworthinessmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with Dharmesti et al (2021), the current results also suggest that YRIs tend to search for information on various online platforms such as social media apps. According to Shaheen et al (2020), information such as online reviews seems to be helpful in building trust among members of the younger generation.…”
Section: Jframentioning
confidence: 99%
“…Also, Gunasekaran, Marri, McGaughey, and Nebhwani (2002) have stated that product availability makes e‐commerce effective. To them, customer satisfaction can only be ascertained when the products are physically in their hands (Leung, Daniel, Mo, Wu, & Huang, 2020; Mangiaracina, Perego, Seghezzi, & Tumino, 2019; Shaheen, Zeba, Chatterjee, & Krishnankutty, 2020). Mangiaracina et al (2019) demonstrate that late delivery has a negative impact on customer satisfaction than a transport or traffic obstacle.…”
Section: Literature Reviewmentioning
confidence: 99%